Kualitas Buku Teks Bahasa Arab MTs Kelas VII: Studi Komparatif Buku Terbitan Kemenag RI dan Dar al-Nile - Roja, Marwah Raisa; Tsabitah, Khansa (Kalimatuna: Journal of Arabic Research, 2024)
This study examines the quality of Class VII Arabic textbooks published by Dar Al-Nile and the Ministry of Religion (Kemenag), based on W.F. Mackey's theory, which encompasses elements of selection, gradation, presentation, and repetition. The book published by the Ministry of Religion aims to support the national curriculum by integrating moderate Islamic values with a context-based thematic approach. In contrast, Dar Al-Nile’s textbook is noteworthy for its application of communicative and phonetic methods, emphasizing speaking skills in a more systematic manner. The researcher employed a descriptive qualitative method, utilizing primary data sources from the Arabic textbooks for MTs Class VII published by the Ministry of Religion of the Republic of Indonesia and Dar Al-Nile. The analysis reveals that the Ministry of Religion’s book excels in the selection of diverse vocabulary that aligns with local needs, while Dar Al-Nile’s textbook is distinguished by its effective material gradation and appealing visual presentation. To enhance contextual and tailored learning experiences for students in Indonesia, this study recommends the development of Arabic textbooks that integrate the strengths of both approaches.